Self-lubricating and wear resistant epoxy composites incorporated with microencapsulated wax - Khun, N. W. (2014)
Self-lubricating and wear resistant epoxy composites were developed via incorporation of wax-containing microcapsules. The effects of microcapsule size and content and working parameters on the tribological properties of epoxy composites were systematically investigated. The incorporation of microcapsules dramatically decreased the friction and wear of the composites from those of the epoxy. The increased microcapsule content or the incorporation of larger microcapsules decreased the friction and wear of the epoxy composites due to the larger amount of released wax lubricant via the rupture of microcapsules during the wear test. The friction of the composites decreased with increased normal load as a result of the promoted wear of the composites and the increased release of the wax lubricant.